RANCANG BANGUN APLIKASI PENGENDALIAN PERSEDIAAN OBAT MENGGUNAKAN METODE SAFETY STOCK DENGAN PERHITUNGAN SERVICE LEVEL BERBASIS WEB PADA APOTEK DELTASARI - Renodicto, Renodicto; Setyawan, Henry Bambang; Wurijanto, Tutut (Jurnal Sistem Informasi Universitas Dinamika, 2020)
Apotek Deltasari Sidoarjo is a pharmacy that is developing and developing in the drug trade or pharmacy sector for people who have health problems. This pharmacy also serves the purchase of medicines both from prescription and non-prescription. The business process includes purchasing, drug inventory, and selling. All business processes are still carried out manually, such as recording inventory data, buying and selling are still carried out in books. As a result, many things occur in pharmacy operational problems such as unserved customer demand due to drug supplies. To overcome this problem, a system is needed that can help pharmacy operations, which includes processing data on supplies, purchases and sales. From the test results, the application that has been made can help process inventory data and process data on receipt of purchased goods, make it easier to manage stock, assist in the sales process, help control drug stocks that must be provided, and can produce stock reports and sales recaps from business processes. who runs the pharmacy.